Desain Konstitusional Pengawasan Parlementer di Indonesia: Antara Kewenangan Normatif dan Realitas Politik - Siti Fatimah; Muhammad Adib Alfarisi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
The inconsistency of institutional design in the modern democratic system has an impact on the weakening of the legislative oversight function and the occurrence of a shift in accountability mechanisms. This is influenced by the dominance of the government coalition in parliament, the weak role of the opposition, the limitation of supervision instruments and follow-ups, structural constraints and institutional capacity, and a political culture that tends to be compromised. This phenomenon reflects an imbalance in the checks and balances mechanism. Thus, the main problem does not lie in the absence of the authority of the DPR, but in the political and institutional conditions that have not supported the effective implementation of the supervisory function. This article aims to analyze the constitutional design of the supervisory function of the House of Representatives in the 1945 Constitution of the Republic of Indonesia and evaluate its effectiveness in constitutional practice. The problems studied focus on the gap between normative forces and empirical reality, where a formally strong institutional design is not always aligned with implementation in the field. This study uses normative legal methods with constitutional, conceptual, and comparative approaches, and is supported by the theoretical framework of separation of powers, checks and balances, horizontal accountability, and judicialization of politics. The results of the study show that normatively, Article 20A of the 1945 Constitution has provided a strong basis for the House of Representatives in carrying out its supervisory function through the right of interpellation, the right of inquiry, and the right to express opinions. However, in practice, the effectiveness of these functions is greatly influenced by political dynamics, especially the dominance of government coalitions and weak opposition, as well as structural constraints in the form of limited sanctions and follow-up mechanisms. This condition causes the supervisory function of the House of Representatives to not run optimally and triggers a shift in the supervisory role to judicial institutions, especially the Constitutional Court. Therefore, the effectiveness of legislative oversight is determined not only by the strength of the constitutional design, but also by political dynamics and institutional capacity. Thus, it is necessary to strengthen institutional design and political reforms to ensure that the oversight function of the House of Representatives can run effectively within the framework of the presidential system and the principle of horizontal accountability.